Diagnostics and Repairs of Damage of the Leaning Tower in Zabkowice Slaskie - Abel, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the diagnosis of the technical condition, as well as the possibilities of renovating, the Leaning Tower located in Zabkowice Slaskie in Lower Silesia, Poland. Damage to the structure of the facility, which occurred in 2015, constituted the basis for carrying out tests and measurements in order to enable the causes of the damage to be determined. The resulting damage is cracks in brick walls.
Keywords: masonry structures; repair of damages; micropiles; belfry; leaning tower; historic building; Ząbkowice Śląskie; konstrukcje murowane; naprawa; mikropal; dzwonnica; krzywa wieża; budynek historyczny